Relativitas Budaya dan Berlangsungnya Budaya Bacha Bazi di Afganistan Pasca Pemerintahan Taliban - Dwi Ramadhani; Satwika Paramasatya (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2020)
This research explains the issue of opposing human rights carried out by the people of Afghanistan against boys through the bacha bazi culture. The conservative culture in Afghanistan led to a separation between men and women, thus bacha bazi serves to be a means of fulfilling the sexual needs of the male community in Afghanistan. “Women are for children, boys are for pleasure” is a famous sentence that explains the culture of bacha bazi for the people of Afghanistan. Although very normal, bacha bazi is taboo to talk about so that the practice is done in secret. The Taliban regime in 1996-2001 was able to abolish the bacha bazi culture, but with the fall of the regime, this culture is increasingly spreading. Domestic and international organizations, as well as foreign troops in Afghanistan, have sought to eradicate the culture, but have encountered difficulties. So this research was conducted to answer how the bacha bazi culture can take place after the Taliban government. The research methodology is an explanative qualitative method through data collection techniques with a literature study. The results of this study are proof that cultural relativity keeps this culture going on in Afghanistan despite violating human rights.